An Assessment of Education Quality in Private Schools - Cueto Huayascachi, Rosa Katherine (2020)
The objective of this research project was to evaluate the quality of private school education in the Chaclacayo District of Lima. The study was performed with a qualitative, descriptive methodology. The quality of education at five private high schools was assessed using a sample of 209 participants, including students, teachers and parents. Three questionnaires were applied: the first with 108 questions for students, the second with 121 questions for teachers, and the third with 83 questions for parents. Results showed that the level of education at these schools was found to be “medium quality”, according to the assessed criteria: customer satisfaction (50.23%), educational leadership (51.37%), strategic planning applied to education (48.30%), human talent satisfaction (51.67%), human talent management (48.15%), teaching methods and processes (51.13%), impact on society (52.80%), educational outcomes (50.17%) and educational resources (47.93%). In conclusion, the quality of high school private education in the Chaclacayo District is found to be at a medium level, represented by a score of 50.93%, according to the average perceptions of the external customers (students and parents), as well as internal customers (teachers).